Prevalence of Candida species in Turkish children: relationship between dietary intake and carriage - AKYÜZ, SERAP HATİCE; KADİR, TANJU (PERGAMON-ELSEVIER SCIENCE LTD, 2005)
In this study, the prevalence and intensity of Candida species were evaluated in 300 healthy Turkish children aged between 0 and 12 years. The candidal carriage in 26 children who were fed only with breast milk and 38 children who were fed with both breast milk and bottle milk or other fluids was also examined. Oral samples cultured for fungal growth and Candida species were identified using germ tube test, chlamydospore formation test and API 20C AUX system. The results demonstrated that the prevalence of oral candidal carriage in 300 healthy children was 26.3%. Candida albicans was the most frequently isolated yeast (84.8% of the isolates). The other yeasts were identified as Candida parapsilosis, Candida krusei, Candida kefyr, Candida famata, and Candida tropicalis. It was also observed that the frequency of carriage varied as a function of age. The prevalence of carriage in children who were fed with both breast milk and bottle milk or other fluids was 18.5%, while in children fed only with breast milk was 0%. This finding supports previously reported observations that there may be intrinsic differences in oral carriage of Candida species between different ages and populations and type of dietary intake may affect frequency of carriage. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Candida; diet; children; HUMAN-MILK; ORAL CANDIDOSIS; ALBICANS; YEAST; SALIVA; FREQUENCY; IMMUNITY; GLUCOSE; INFANTS; GROWTH